Minimalisme moral et maximalisme éthique chez John Dewey - Michel Fabre (Nantes Université, 2014)
John Dewey'Ethics is a paradoxical thought, both secularizing Moral theory and keeping a requirement of Ethics of Grown. On the one hand Dewey against Eudaemonism, utilitarianism and kantism, refuses any moral principles a priori. He advises an free analysis of problematic situations characterized by conflicting values​​. In such a contextualism, principles become mere tools of intelligibility and resolution of a problematic situation in which the actors are involved. Dewey also refuses the dualisms of moral tradition: the Hume's rule, the gap between ends and means. Rejecting any idea of Moral Consciousness or Practical Reason as separate faculties, but also ethical Emotivism, he advises ethical debate, an act of common intelligence applied to live together. On the other hand, from Emerson's tradition, he takes, through all his writings, that life is education, grown, moral perfection. The requirement of grown'ethics is, for him, a counterweight to the secularization of morality. What about this articulation between moral minimalism and maximalism of ethics?